A Study on the Influence of Internet Information Literacy on the Learning Behaviors of Senior High School Students - Daud, Khalid (RADINKA JAYA UTAMA PUBLISHER, 2024)
This study explored the attitudes of Senior High School students toward using the Internet as a tool for information literacy. It aimed to examine how students utilize the Internet in their education and daily lives, focusing on the extent, purpose, and location of its use. The Internet has revolutionized access to information, offering opportunities to enhance learning and improve critical thinking skills. A descriptive research design was employed, and data were gathered through a self-constructed questionnaire administered to 85 respondents selected via stratified random sampling. The questionnaire included demographic profiles and indicators to assess students’ attitudes toward Internet Information Literacy (IIL). Key findings revealed that the Internet plays a crucial role in providing diverse information sources and fostering learning opportunities beyond traditional classroom methods. The results underscored the significance of equipping students with critical evaluation skills to optimize their Internet use in education. Furthermore, the study highlighted the Internet's potential to empower students by offering personalized and flexible learning experiences. These findings suggest that fostering Internet Information Literacy among students is essential to lifelong learning and effective education in the digital age.